DETERMINATION OF NUTRITIVE VALUE AND ANTI-METHANOGENIC POTENTIAL OF TURKISH GRAPE POMACE USING IN VITRO GAS PRODUCTION TECHNIQUE - A. I. Atalay (Journal of Animal and Plant Sciences, 2020)
Grape pomace from the wine industry has been used in ruminant nutrition to meet the requirements of animals during shortages of conventional feed in most parts of the world. The aim of the current study was to screen Turkish grape pomaces (GPs) collected from various sites for chemical composition and anti-methanogenic potential using an in vitro gas production technique. Source had a significant effect on the chemical composition, gas production, methane (CH4) production, metabolizable energy (ME), and organic matter digestibility (OMD) of some Turkish GPs. Crude ash (CA), ether extract (EE), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), condensed tannin (CT) contents, gas production, CH4 production, ME, and OMD values of the GPs were in the ranges of 3.90-9.37%, 3.07-7.87%, 2.65-13.50%, 26.60-58.80%, 24.98-53.88%, 1.99-16.43%, 42.75-113.50 mL, 5.57-13.38 mL, 5.36-8.69 MJ/kg DM, and 39.87-61.27%, respectively. The in vitro experiment showed that most of the GP samples studied have low CH4 mitigation potential. However, there is a need for in vivo experiments to test the mitigating potential of GP samples.
Keywords: Grape pomace; chemical composition; digestibility; methane production